STUDYING THE WISDOM OF ZAKAT - Moch. Gatot Koco; Basuki R Suratno (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Zakat is the fifth pillar of Islam that must be done by every Muslim who is able to issue it, both zakat private (zakat fitrah) and zakat karta wealth (zakat maal), to be accepted to the person entitled to receive it (mustahiqquz zakat) consisting of 8 (Eight) class (asnafus samaniyah) the recipient of zakat, because with zakat will be obtained the wisdom of mandatory orders as a social concern among fellow Muslims muslimin muslimat. In this paper discusses and examines the wisdom of zakat. It is known that Zakat in language is sacred or fertile. Medium in term or syara 'zakat is to remove some of the goods on the order of Allah as a sadaqah obligatory to those who have been determined by Islamic law. Zakat there are 2 (two) kinds of zakat mal and zakat fitrah. Zakat mal includes: gold, silver, money, commercial property, livestock, fruits and grains, minerals and alian goods. The recipients of zakat are: the needy, the poor, the muallaf, the servant of sahaya, the man who has the debt, sabilillah, and the traveler. While the wisdom of zakat is: educating oneself to make sacrifices for the sake of others, a sense of equality with others, understand that he is not living alone, there is togetherness, eliminating the gap between each other and social attitudes high.